Characteristics of Particulate Emissions from Co-Firing in An Industrial Boiler - Ines Saraswati Rudianto (Jurnal Ecolab, 2021)
Characteristics of Particulate Emissions from Co-Firing in An Industrial Boiler. PT. X is a textile industry that consumes a massive amount of coal for its boiler operation. It requires substantial costs to obtain coal from Sumatra and Kalimantan. An alternative solid biofuel (briquette) was developed to combine bottom ash and biomass made from municipal solid waste called Biomass Coal Fuel (BCF) briquette. The purpose of this study is to measure the total concentration of particulate matter and emission factor (PM) emitted from two burning experiments: only coal (100%) and mixed coal fuel with 10% of BCF (co-firing). Mixed coal and BCF burning are carried out in the fire-tube boiler where the PM emission is released through the stack. The Center for Pulp and Paper measured particulate emission with methodology referring to SNI 7117.17-2009. Particulate matter concentration emitted from only coal-burning was 12,1 mg/Nm3,but when mixed BCF and coal were used, the higher concentration was emitted 70,9 mg/Nm3. The addition of BCF briquettes affects the particulate matter emission, even though the emission does not exceed the regulated quality standard. The increase of particulate concentration is due to the BCF briquette characteristics, which have a low heating value and high ash content. The boiler has already been equipped with cyclone and wet scrubber; therefore, PM emissions presented here are treated emissions. The controlled PM emission factor of BCF was 4,46 g/kg, which is higher than only coal which was 0,51 g/kg. BCF briquette can still be used as co-fuel for the boiler, but further effort is still required to reduce the ash content of the BCF and increase the calorific value of the BCF.